The Effect Of Giving Water Vapor Therapy With Gotu Kola Essential Oil (Centella Astiatica) Terhon Respiratory Disorders Of Toddlers At Rismala Clinic In 2022 - Farida Umamy; Nur Aini Dalimunthe; Paramita Mustari; Sri Junita Simaremare (Jurnal EduHealth, 2024)
Background: ineffective breathing pattern is a state where inspiration and / or expiration do not provide adequate ventilation. One of the efforts that can be done to is by way of water vapor inhalation therapy air. Water vapor inhalation therapy air is helpful for removing blockages in the respiratory tract. Steam inhalation therapy can be done by adding herbal oils such as Gotu Kola essential oil to enhance the effect of the treatment. The purpose of this study was to analyze the effect of steam inhalation therapy with Gotu Kola essential oil on the ineffectiveness of breathing patterns in children. Research Methods: this study is a literature review study using 2 articles adapted to the inclusion criteria and analyzed qualitatively. Results of the study : based on the results of both articles showed that there was an increase in breath patterns before and decreased breath patterns after being given Gotu Kola essential Oil steam inhalation therapy and there was an effect of steam inhalation therapy with Gotu Kola essential Oil on the ineffectiveness of breath patterns in toddlers. Conclusion : it can be concluded that in both articles, the results obtained are the effects of steam inhalation therapy with eucalyptus oil on the ineffectiveness of breath patterns in children keywords: inhalation, Eucalyptus Oil, breath patterns